1996
DOI: 10.1038/ng0596-95
|View full text |Cite
|
Sign up to set email alerts
|

A R59W mutation in human protoporphyrinogen oxidase results in decreased enzyme activity and is prevalent in South Africans with variegate porphyria

Abstract: Variegate porphyria (VP), a low-penetrant autosomal dominant inherited disorder of haem metabolism, is characterised by photosensitivity (Fig. 1) and a propensity to develop acute neuropsychiatric attacks with abdominal pain, vomiting, constipation, tachycardia, hypertension, psychiatric symptoms and, in the worst cases, quadriplegia. Acute attacks, often precipitated by inappropriate drug therapy, are potentially fatal. While earlier workers thought the distal haem biosynthetic enzyme ferrochelatase may be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 14 publications
3
185
0
4
Order By: Relevance
“…Recently, this mutation has been documented as the first mutation in AIP associated with a founder effect in North America with the identified founding couple (Greene-Davis et al 1997). Such a founder effect has been well documented in variegate porphyria, the other form of acute porphyria (Dean 1971;Meissner et al 1996;Warnich et al 1996;Groenewald et al 1998), and has also been observed in other AIP patients (De Siervi et al 1999). The other mutation in Japan, reported by Morita et al (1995), is a single base substitution C-to-T in exon 8 of the gene, which was the same as a common mutation in the Netherlands (Gu et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this mutation has been documented as the first mutation in AIP associated with a founder effect in North America with the identified founding couple (Greene-Davis et al 1997). Such a founder effect has been well documented in variegate porphyria, the other form of acute porphyria (Dean 1971;Meissner et al 1996;Warnich et al 1996;Groenewald et al 1998), and has also been observed in other AIP patients (De Siervi et al 1999). The other mutation in Japan, reported by Morita et al (1995), is a single base substitution C-to-T in exon 8 of the gene, which was the same as a common mutation in the Netherlands (Gu et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…VP mutations also show high heterogeneity with the exception of founder effect mutations e.g. mutation R5 9W in South Africa [7,19].…”
Section: Variegate Porphyriamentioning
confidence: 99%
“…AIP prevalence in Argentina is about 1/125 000 inhabitants [6]. VP is most frequently reported in South African Republic (1/300 inhabitants) due to founder effect [7]. VP prevalence in Finland is estimated at 2/100 000 inhabitants [8]; in Argentina at 1/600 000 [6].…”
Section: Epidemiology Datamentioning
confidence: 99%
“…6 Genetic analysis would be the only reliable tool to establish a correct diagnosis of Porphyria even though the high genetic heterogeneity makes this approach difficult. Although restricted geographic areas seem to have a high prevalence of specific molecular abnormality, 7 most of the reported mutations have been detected in a single case or a family. [8][9][10] Moreover, approximately 10% of porphyria cases remain devoid of molecular diagnosis.…”
Section: Introductionmentioning
confidence: 99%